Assertiveness educational interventions for nursing students and nurses: A systematic review. (January 2023) - Lee, Seung Eun; Kim, Eunkyung; Lee, Ji Yea; Morse, Brenna L.
Abstract: Objectives: The purpose of this study was three-fold: to (1) synthesize evidence from experimental studies regarding educational interventions for developing nursing students' and nurses' assertiveness, (2) examine such interventions and identify their effective components, and (3) recommend future research considerations in this area. Design: A systematic review of the literature. Data sources: Literature searches were conducted using three electronic databases (PubMed, CINAHL, and PsycINFO) in addition to hand searches to identify original research articles published between 2012 and 2022. Review methods: Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were followed for the systematic review and reporting process. Included studies were critically appraised using the Joanna Briggs Institute Critical Appraisal Checklists. Results: Fourteen articles were included in this review, with most of the studies conducted in Asian countries. Four intervention methods were used for assertiveness education across the studies: (1) simulation-based learning, (2) classroom-based learning, (3) classroom-based learning with peer support, and (4) hybrid learning. Classroom-based learning interventions were the most common. Among all types of interventions, key concepts included assertiveness, differentiating between assertive and non-assertive behaviors, and assertive communication skills. Most studies measured participants' speaking-up behaviors by self-report. Mixed results were observed in terms of intervention effectiveness, but providing participants with opportunities to practice assertive communication skills benefited their speaking-up. Conclusions: Educational interventions can strengthen the skills, confidence, and capacity of current and future nurses to employ assertive communication. Intervention developers should create programs that involve classroom teaching and provide participants with opportunities for practice, either through simulation or role-play. Also, researchers should observe participants' post-intervention use of assertive communication in simulations or clinical practice as opposed to surveying participants' intention to speak up.